Faire nation par la mine ? Histoire politique des territoires miniers au Groenland - Bailleul, Pia (Études Inuit Studies, 2024)
International audience Nation building through mining ? A political history of mining territories in Greenland -- Greenland is engaged in state extractivism to support the strategy of gaining independence through mining rents. After a decade of conflict, a form of national unity, from the government to the population, is emerging around mines located far from localities, or small-scale local mines. How can we understand the return of this model, blamed in the 1980s and historically the vector of an enclave phenomenon criticized in Greenland’s history ? Distancing myself from the Not in my backyard and political approaches, which approach this question from the angle of mining compromises for independence, I propose to grasp it from a historical perspective of the political and social stakes of mining. The article draws on ethnographic and bibliographic data to draw up a history of the Greenland minescape, in other words, of the social worlds and political issues emerging from mining practices. It reveals an association between mining and nationalism in the representation and identification of a political territory, and analyzes contemporary extractivism and its extraction models as a renewal of the national imaginary of territory. Le Groenland est engagé dans un extractivisme d’État pour soutenir la stratégie d’accession à l’indépendance par la rente minière. Après une décennie de conflit, une forme d’union nationale, allant du gouvernement à la population, émerge autour de mines éloignées des localités ou de mines de petites tailles de proximité. Comment comprendre le retour de ce modèle, blâmé dans les années 1980 et historiquement vecteur d’un phénomène d’enclave critiqué dans l’histoire du Groenland ? Se distanciant des approches Not in my backyard et politistes, qui abordent cette question sous l’angle des compromis minier pour l’indépendance, je propose de la saisir dans une perspective historique des enjeux politiques et sociaux du minier. L’article s’appuie sur des données ethnographiques et ...